(untitled) (GEOmedia, 2010)
Location of buildings unknown to Cadastre Records This article addresses the issue of updating census, parcel and cadastral data for buildings which have not yet been registered. A campaign of quasi-automatic detection was carried out using the integration of the cadastral map with Earth Observation digital technologies and terrain modeling. From 2007 to 2009, many out of date parcels were updated during the campaign. The campaign, is the result of a positive collaboration between government agencies and private companies.